A new Afrotropical genus Monocentroptilum gen. n. (Ephemeroptera: Baetidae: Protopatellata) - Kluge, Nikita J. (Zootaxa, 2018)
A new genus Monocentroptilum gen. n. is established for a single Afrotropical species, originally described as Centroptilum badium Kopelke 1980 from Congo. Larvae, subimagoes, imagoes of both sexes and eggs of Monocentroptilum badium comb. n. are described here based on reared material from Uganda.